Does Information Empower the Poor? Evidence from Indonesia's Social Security Card - Achmad Tohari; Christopher Parsons; Anu Rammohan (Institute of Labor Economics (IZA), 2017)
In 2013, the Government of Indonesia conducted one of the largest information interventions in histo-ry, in an attempt to further alleviate poverty and as a complement to the Social Protection Card (KPS). Drawing upon administrative data and nationally representative surveys, we evaluate the impact of the information campaign on the receipt of two of Indonesia's largest social programs, the Raskin (rice for the poor) and the BLSM (temporary unconditional cash transfers). Exploiting the design of the Raskin program, we implement a (normalised) fuzzy regression discontinuity methodology across 482 Indonesian districts, using program eligibility as an instrument for having received the information treatment. Further corroborating our results with semi-parametric and parametric techniques, we show that the information treatment increases the amount of rice received under the Raskin program by around 30 percentage points. In terms of the BLSM, we further show that the information treatment reduces the likelihood of elite capture by local leaders by around 25 percentage points. We also provide evidence that understanding the information treatment is crucial for poor household's out-comes, since fully informed households receive their full entitlement of rice.
Keywords: D04; D73; I32; I38; O12; 330; information; Indonesia; targeting; poverty